2010
DOI: 10.3892/mmr_00000296
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin in cancer: A new mission for an old agent

Abstract: Abstract. Salinomycin is a monocarboxylic polyether ionophore isolated from Streptomyces albus that has been used for more than 30 years as an agricultural antibiotic to prevent coccidiosis in poultry and to improve nutrient absorption and feed efficiency in ruminants and swine. As a inonophore with strict selectivety for alkali ions and a strong preference for potassium, salinomycin interferes with transmembrane potassium potential and promotes the efflux of K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 36 publications
1
66
0
4
Order By: Relevance
“…This compound is now considered an important anticancer drug candidate (17,18). It has recently been reported that salinomycin can selectively kill human breast cancer stem cells, and is 100-fold more effective at reducing the proportion of CSCs than paclitaxel, albeit by an unknown mechanism (19).…”
Section: Introductionmentioning
confidence: 99%
“…This compound is now considered an important anticancer drug candidate (17,18). It has recently been reported that salinomycin can selectively kill human breast cancer stem cells, and is 100-fold more effective at reducing the proportion of CSCs than paclitaxel, albeit by an unknown mechanism (19).…”
Section: Introductionmentioning
confidence: 99%
“…Salinomycin-induced apoptosis in human cancer cells is mediated by an uncommon pathway and independent of typical mechanism like activated caspases, death receptors like the CD95/DC95 ligand system or tumor suppressor protein p53 [15,19]. Demonstrating that Salinomycin-induced apoptosis in human CC cells is independent of caspase-3 activation confirms that apoptosis is mediated through an uncommon pathway.…”
Section: Discussionmentioning
confidence: 49%
“…However, the exact mechanisms by which Salinomycin induces apoptosis are still incomplete understood [15]. Salinomycin-induced apoptosis in human cancer cells is mediated by an uncommon pathway and independent of typical mechanism like activated caspases, death receptors like the CD95/DC95 ligand system or tumor suppressor protein p53 [15,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinomycin is a polyether ionophore that was originally used as an antibiotic to prevent infectious diseases in poultries (12). Recently, cytotoxic effects of this drug on human neoplastic cells have been demonstrated in various types of cancer (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%